Over-the-counter fish oil supplementation and pro-resolving and pro-inflammatory lipid mediators in rheumatoid arthritis. (March 2023) - Marchand, Nathalie E.; Choi, May Y.; Oakes, Emily G.; Cook, Nancy R.; Stevens, Emma; Gomelskaya, Natalya; Kotler, Gregory; Manson, JoAnn E.; Lasky-Su, Jessica; Mora, Samia; Lee, I-Min; Tatituri, Raju; et al.
Highlights: Fish oil supplements contain omega-3 fatty acids from which specialized pro-resolving mediators (SPM) are derived, including resolvins, protectins, and maresins. These have potential as therapy for human rheumatic inflammatory disease, however, little is known about the effect of fish oil supplementation on SPM blood levels in rheumatoid arthritis patients. But, previous research has shown that fish oil supplementation is associated with a lower risk of RA. Thus, we investigated associations between over-the-counter omega-3 fatty acid FO supplementation and circulating SPMs among patients with and without RA. Among all patients, both with and without RA, oral over-the-counter fish oil supplementation was associated with higher blood levels of pro-resolving lipid mediators including 17-HDHA (from DHA) and 15- and 18-HEPE (from EPA), precursors of both protectins and resolvins. RA patients have the ability to augment their SPM precursor reserves, which may be important in resolving RA inflammation. Abstract: Objective: Little is known about the effects of over-the-counter fish oil (FO) supplements on circulating omega-3 polyunsaturated fatty acid (n-3 PUFA)-derived specialized pro-resolving mediators (SPMs), nor about whether having a chronic inflammatory disease such as rheumatoid arthritis (RA) influences SPM levels. We investigated associations between over-the-counter n-3 PUFA FO supplementation and circulating SPMs among patients with vs. without RA. Methods: We studied 104 participants: 26 with RA taking FO matched by age and sex to 26 with RA not taking FO, 26 without RA taking FO, and 26 without RA not taking FO. Targeted-liquid chromatography-tandem mass spectroscopy was performed on patient plasma to identify and quantify 27 lipid mediators (including eicosanoids and SPMs). We performed t-tests and then multivariable linear regression analyses to assess whether having RA or taking FO supplements was associated with circulating lipid mediator concentrations, adjusting for age, race, sex, smoking, body mass index, and current medication use (statins, prednisone and immunomodulators among RA cases only). We tested for interactions between FO supplementation and RA status. We also conducted Spearman's correlations between EPA, DHA, and ARA and their downstream metabolites. Results: Among patients who were taking FO compared to those who were not, in multivariable- adjusted analyses, SPM substrates EPA and DHA were both elevated as were several of their pro-resolving bioactive products, including 15- and 18-HEPE from EPA, and 14- and 17-HDHA from DHA, which are substrates for specific SPMs. While E-series and D-series resolvins were present and identified, we did not find statistical elevations of other SPMs. Results were similar among patients with RA and patients without RA, taking vs. not taking FO supplementation (no formal statistical interaction observed). There was a strong positive correlation between EPA and DHA and their immediate downstream SPM precursors (18-HEPE and15-HEPE from EPA; 17-HDHA and 14-HDHA from DHA) among all patients. Conclusion: Patients taking FO supplements, regardless of RA status, not only had higher blood levels of EPA and DHA, but also of their enzymatic products 18-HEPE (E-series resolvin precursors), 15-HEPE and 17-HDHA (D-series resolvin and protectin precursors). Patients with RA, an inflammatory autoimmune disease, may be able to augment some SPM precursor reserves, similarly to matched controls without RA, by taking oral FO supplements.